Improved survival trends in platinum-resistant patients with advanced ovarian, fallopian or peritoneal cancer treated with first-line paclitaxel/platinum chemotherapy: The impact of novel agents - Bamias, A.; Bamia, C.; Zagouri, F.; Kostouros, E.; Kakoyianni, K.; Rodolakis, A.; Vlahos, G.; Haidopoulos, D.; Thomakos, N.; Antsaklis, A.; Dimopoulos, M.-A. (Oncology (Switzerland), 2013)
Objective: The prognosis for patients with platinum-resistant advanced ovarian cancer remains poor. The impact of approved agents on survival has not been clarified during the last decade. We studied survival trends during the last 15 years in platinum-resistant patients treated with cytoreductive surgery followed by paclitaxel/platinum chemotherapy. Methods: Patients with epithelial ovarian, fallopian or peritoneal cancer, stages III/IV and platinum-resistant disease after first-line chemotherapy with paclitaxel/platinum were included. They were grouped according to the period of chemotherapy: group A 31/3/1995-31/12/2001 (n = 56) and Group B 1/1/2002-24/12/2008 (n = 57). In order to compensate for the difference in follow-up between the 2 groups, we performed minimum follow-up (MFU) analyses by considering as cases only women who had an event within 3 years of follow-up. Patients with no events for up to 3 years were censored at that time. Results: MFU analyses showed that median overall survival (OS) was significantly longer in group B: 12.3 vs. 17.5 months (p = 0.012). This was due to a doubling of the median OS after relapse: 5.7 vs. 10.9 months (p = 0.0180). Multivariate Cox regression indicated group and histology as factors statistically significantly associated with OS. Following relapse, patients in group B were predominantly treated with liposomal doxorubicin and gemcitabine, and patients in group A were treated with platinum compounds, docetaxel and oral etoposide (p < 0.001). Conclusions: The introduction of novel agents without cross-resistance to platinum or taxanes has improved the prognosis of platinum-resistant patients. © 2012 S. Karger AG, Basel.
Keywords: Chemotherapy; Ovarian cancer; Platinum-resistant